Research Progress on Sublethally Injured of Microorganisms Induced by Non-thermal Processing Technologies and Its Control Methods - Bohua WANG; Qisen XIANG; Yanhong BAI (Shipin gongye ke-ji, 2023)
In recent years, non-thermal processing technologies have been received great attentions for their potential application in food sterilization and preservation. However, various studies have showed that some non-thermal processing can cause sublethal injury of microbial cells. Sublethal injury of microorganisms refers to a physiological state in-between life and death, which may represent a potential risk for food safety. This article aimed to review the latest research progress in the formation of sublethally injured microorganisms induced by non-thermal processing technologies, such as pulsed electric field, high-pressure carbon dioxide, cold plasma, and high hydrostatic pressure. In addition, the detection and control methods of sublethally injured microbial cells are also reviewed in this article. Finally, the prospects for future research in the area are also discussed. This review provides a theoretical basis for the research of sublethal injury microorganisms and their control techniques.